2005
DOI: 10.1177/0091270004273343
|View full text |Cite
|
Sign up to set email alerts
|

A Combined‐Formulation Tablet of Lamivudine/Nevirapine/Stavudine: Bioequivalence Compared With Concurrent Administration of Lamivudine, Nevirapine, and Stavudine in Healthy Indian Subjects

Abstract: Generic fixed-dose combinations of antiretrovirals are frequently prescribed for the treatment of human immunodeficiency virus infection. A randomized, 2-way study was conducted in 24 fasting, healthy, Indian male subjects to assess bioequivalence between a single combination tablet containing lamivudine, stavudine, and nevirapine (treatment A) with respect to separate marketed tablets administered simultaneously (treatment B). Each subject received treatments A and B separated by 19 days of a drug-free washou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…In a healthy volunteer study, the pharmacokinetic (PK) parameters of the generic FDC of d4T/3TC/NVP was compared to PK parameters of the three branded products, administered simultaneously [5]. Because this was a cross-over study, the patients were used as their own control.…”
Section: Introductionmentioning
confidence: 99%
“…In a healthy volunteer study, the pharmacokinetic (PK) parameters of the generic FDC of d4T/3TC/NVP was compared to PK parameters of the three branded products, administered simultaneously [5]. Because this was a cross-over study, the patients were used as their own control.…”
Section: Introductionmentioning
confidence: 99%
“…Both these methods require a total run time of 10 min or more on C-18 reverse phase columns. Recently Narang et al [41] have developed a high throughput LC-MS/MS method to quantify 3TC, d4T and NVP in human plasma with special reference to bioequivalence study. Extraction of plasma was done by SPE involving a reconstitution step to get a LLOQ of 50, 51 and 47 ng/mL for 3TC, d4T and NVP, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Since, the logP of 3TC and d4T is −1.11 and −0.81, respectively, LLE is not suitable for these two NRTIs. Recently, Narang et al (2005) and Mistri et al (2007) described an SPE method. However, the sample preparation process was quite time-consuming and not suitable for high throughput sample analysis.…”
Section: Development Of the Sample Preparingmentioning
confidence: 99%
“…Aymard et al (2000) and Notari et al (2006) have reported simultaneous determination of these three drugs with other NRTIs, NNRTIs and PIs in human plasma by HPLC-UV with a run time of 40 or 35 min and volume of plasma of 1 or 0.6 mL. LC-MS/MS methods for simultaneous quantifi cation of 3TC, d4T and NVP in human plasma were described by Narang et al (2005), and Mistri et al (2007) used a C 18 reversed-phase column and acid mobile phase with solid-phase extraction (SPE). The lower limit of quantitation (LLOQ) was from 51 to 20 ng/mL.…”
Section: Introductionmentioning
confidence: 99%